Enchantment and Lived Experience in Contemporary Actor's Art (Global Journal of Human-Social Science, 2025)
This is an empirical account of audience engagement as part of an academic study by the Federal University of Paraíba. The article explores the role of ephemerality in contemporary theatrical performance, emphasizing its impact on audience reception and their intersubjective experience. Thus, the experience described here points to the ephemeral as a tool for creating enchantment. The reflection focuses on the audience's reaction to the words and actions of a performer juggling at the entrance to a theatre in João Pessoa, Brazil. References include Lev Semionovich Vygotsky's proposal on the psychology of actor-creation, as well as the relational aesthetics described by Nicolas Bourriaud. The study detects a possible connection between what is understood as a mirror neuron and the Russian term "perezhivanie," highlighting the degree of emotional engagement of the spectator and reflecting on the active role of the audience in a theatrical performance. Through an interdisciplinary analysis, this case study aims to effectively contribute to artistic research methodology and contemporary theatrical practices.
Keywords: staging; juggling; theatrical play; the ephemeral on stage; performance art; circus activity